Attempts to evaluate locus suicide recombination and its potential role in B cell negative selection in the mouse - Denis-Lagache, Nicolas; Oblet, Christelle; Marchiol, Tiffany; Baylet, Audrey; Têteau, Ophélie; Dalloul, Iman; Dalloul, Zeinab; Zawil, Lina; Dézé, Ophélie; Cook-Moreau, Jeanne; Saintamand, Alexis; Boutouil, Hend; et al. (Frontiers in Immunology, 2023)
In mature B cells, Activation-Induced Deaminase (AID) reshapes immunoglobulin (Ig) genes through somatic hypermutation (SHM) of V regions and class switch recombination (CSR) of the Ig heavy chain (IgH) locus under control by its 3’ cis-regulatory region (3’RR). The IgH 3’RR is itself transcribed and can undergo AID-mediated “locus suicide recombination” (LSR), then deleting the IgH constant gene cluster and terminating Ig expression. The relative contribution of LSR to B cell negative selection by comparison to other cell death pathways remains to be determined. Which B cell compartment or activation pathway is most exposed to LSR is notably unknown. By setting up a reporter model for LSR events, we evaluated their occurrence along various conditions of B-cell activation, and notably in antigen-experienced B-cells. Study of mice in which the IgH locus sequences targeted by LSR are truncated or deleted, additionally suggested that LSR may contribute to the elimination of self-reactive B-cells.